What's the purpose? Educators' perceptions and use of a state-mandated kindergarten entry assessment - Hattie Harvey; Kathryn Ohle (Arizona State University, 2018)
Educator's perceptions and use of a state-mandated kindergarten entry assessment (KEA), the Alaska Developmental Profile (ADP), were investigated using a mixed-methods approach with 233 educators representing 23 districts in the state of Alaska. Educators reported inconsistencies in the administration, implementation, perceptions, and use of the ADP. These inconsistencies were connected to an unclear understanding of the purpose for the ADP, a finding that most likely reflects the compliance model of those administering state-mandated assessments instead of educators seeing these tools as useful for instructional decision-making. Results suggest policy makers should strive to ensure all stakeholders have a clear understanding of the purpose for a state-mandated KEA and that systems are in place to ensure reliability and validity of the data. Teachers are urged to become familiar in using formative, observation-based assessment approaches and consider how data gathered from a KEA can provide meaningful information for instructional planning. Administrators are encouraged to provide the professional development and support needed to engage in data-driven decision making. And finally, researchers are reminded of their role in helping conduct research that examines the processes and impact of state-mandated assessments.